Implementation of video tutorial-assisted worksheets to improve the learning outcomes of junior high school students on environmentally friendly technology - Rini Yunita Rahman; Laifa Rahmawati; Salma Samputri (Universitas PGRI Pontianak, 2026)
Effective learning requires innovative instructional media. This study aimed to determine (1) the improvement in learning outcomes following the implementation of video tutorial-assisted worksheets among students of SMP Nasional Makassar, and (2) whether there was a significant difference in learning outcomes before and after the implementation of video tutorial-assisted worksheets. This study employed a pre-experimental method with a one-group pretest-posttest design. The population comprised all ninth-grade students of SMP Nasional Makassar, totaling 179 students, from which a sample of 32 students was selected through purposive sampling. Learning outcomes were measured using a multiple-choice test that had been developed and validated prior to implementation. Data were analyzed descriptively and inferentially. The results showed that (1) learning outcomes improved, as indicated by an N-Gain of 0.51 (moderate category), and (2) there was a statistically significant difference between pretest and posttest scores after the implementation of video tutorial-assisted worksheets, as indicated by a significance value of less than 0.05. These findings demonstrate that worksheets combined with video tutorial media have a positive impact on the science learning process and help improve students’ understanding and learning outcomes.